(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
The latest Credit Derivatives Determination Committee 2021, established by the top bank Reserve Bank of India (RBI), outlines the way forward for the credit derivatives market. Indian derivatives are equities, bonds, commodities and currencies. The Bombay, the National Stock Exchange and the Multi Commodity Exchange are accessible. However, the banks’ market for credit derivatives or securitisation is mostly absent. This is one of the most important components of the developed economy worldwide. The primary feature of the credit derivative is that it transfers the risk of the originator to investors who are ready to accept the risks and be exposed to the market to diversify their investments. One benefit of bank credit derivatives is that it lowers deposit dependence as capital and makes banks more accountable to manage their risk exposure. Not to add accountability and transparency, because they are evaluated by credit rating agencies, when it issued the credit derivatives. Credit derivatives are designed to transfer risk, call risk, and credit risk. The purpose of this study is to analyse the possibilities and difficulties of the market in credit derivatives in India, particularly for banks that are undercapitalized and have significant problems with their repayment. How this would also alter the whole market from an investment perspective. This article also presents the idea of credit derivatives and its many histories and aspects at their inception. The article is conceptual in nature and serves to establish a path ahead for future study when the market peaks. However, RBI issued the previous circular in 2011 under the heading of "Revised Credit Default Swap (CDS) Guidelines for Corporate Bonds," which did not fully explore the market’s potential. Almost ten years later, the current circular on the creation of the committee of 2021 looks forward to its recovery and reduces the dependence of the banks on its traditional sources of funding. Only time will tell how far it was accomplished in the Indian banking industry with so many difficulties.